Eigenvalues and their participation factors for the system of coupled adjacent microgrids - Shahnia, Farhad (2017)
© 2016 IEEE.Adjacent islanded microgrids may couple provisionally to support each other during emergencies such as overloading in one MG. Thus, a microgrid will observe a structural transformation, when coupled with one/more adjacent microgrids. Before this transformation, the stability of the new system should be carefully assessed to reject the coupling if instability is probable. This paper uses an eigenanalysis-based small signal stability assessment to investigate the critical eigenvalues of a system of coupled MGs in comparison with the eigenvalues of the MGs which have constituted the CMG, as well as the participation factors of the dominant states on those critical eigenvalues. MATLAB-based numerical analyses are performed for a few sample microgrids.